Leadership dimension: increasing employee satisfaction and engagement in travel industry - Nova Eviana; Rudhi Achmadi (Jurnal Pariwisata Pesona, 2022)
Employee engagement becomes one of the most important driving factors in the success of business processes because it can provide high motivation for the employees' positive behavior and support the achievement of the travel company goals. Positive behavior includes striving to provide the best service and ensure consumer satisfaction. Various studies explain the relationship of employee engagement with leadership and employee satisfaction factors. This study aims to analyze the effect of leadership and employee satisfaction on fostering employee engagement. The research instrument used questionnaires as a data-gathering tool. About 77 travel agency employees participated as respondents based on accidental sampling techniques. Data analysis used SEM-PLS with Smart PLS software. The results showed that leadership affects  employee satisfaction and engagement. Leadership having fair behavior and being accommodative to the employees’ needs and interests will foster employee satisfaction, which ultimately affects employees engagement. Therefore, it is important for the company to improve the leadership factor